Estudio técnico comparativo de las propiedades físicas entre bloques de manpostería tradicional tipo pómez y bloques de mampostería elaborados a base de cascarilla de arroz como agregado orgánico - Maldonado Peñaloza, Henry Mauricio (2015)
This research is mainly based on the production of masonry blocks using rice husk as such without pre treatments, as replacement of traditional added since chasqui used in our environment , they are compared with pumice type blocks, through its physical properties . They have been proposed to compare the physical properties between these two types of blocks , complying with Ecuadorian INEN technical standard for processing and subsequent trials. for block design with rice hulls , they have been raised different dosages , keeping the dimensions of the blocks to be subjected to the main compression tests , density and water absorption